Vincristine Regulates C/EBP-β/TGF-β1 to Promote A1 Astrocyte Polarization and Induce Neuropathic Pain - Chen Y; Tang G; Lu J; Tang S; Xiong X; Chen C; Pei L; Shi J (Drug Design, Development and Therapy)
Yunfu Chen,1,* Guangling Tang,1,* Jun Lu,1,* Sijie Tang,1 Xinglong Xiong,1 Chao Chen,1 Lijian Pei,2 Jing Shi1 1Department of Anesthesiology, The Affiliated Hospital of Guizhou Medical University, Guizhou, People’s Republic of China; 2Department of Anesthesiology, Peking Union Medical College Hospital, Beijing, People’s Republic of China*These authors contributed equally to this workCorrespondence: Jing Shi, Department of Anesthesiology, The Affiliated Hospital of Guizhou Medical University, Guiyang, People’s Republic of China, Tel +86-18685034016, Email shijing81@gmc.edu.cn Lijian Pei, Department of Anesthesiology, Peking Union Medical College Hospital, Beijing, People’s Republic of China, Email hazelbeijing@vip.163.comBackground: The neuropathic pain side induced by Vincristine severely limit its clinical application. However, the mechanism of neuropathic pain is not clear. This study aims to clarify the mechanism of C/EBP-β regulating TGF-β 1 mediated spinal astrocyte A1/A2 polarization in the neuropathic pain caused by vincristine.Methods: Neuropathic pain model was established in rats by intraperitoneal injection of Vincristine (VCR). In vitro experiment, the astrocyte model was constructed by Vincristine, and si-C/EBP-β was regulated before VCR administration. Pain threshold of rats was measured by thermal withdrawal latency (TWL) and mechanical withdrawal threshold (MWT), Elisa was used to detect the expression level of inflammatory factors, qRT PCR and Western blotting were used to detect astrocyte polarization markers, C/EBP-β, TGF-β 1, p-smad2 and p-smad3.Results: Following Vincristine administration, the TWL and MWT of rats exhibited a decrease. Additionally, there was an increase in A1 polarization of astrocytes, while A2 polarization remained relatively unchanged. Furthermore, the expression levels of pro-inflammatory factors were elevated, whereas no significant alterations were observed in anti-inflammatory factors. Notably, Vincristine promoted the expression of C/EBP-β and TGF-β 1. TGF-β 1 inhibitor alleviated VCR induced astrocyte A1 polarization and release of proinflammatory factors, ameliorated abnormal pain. Moreover, silencing C/EBP-β reversed the enhanced expression of TGF-β 1 induced by Vincristine, attenuated astrocyte A1 polarization and proinflammatory factor release.Conclusion: Vincristine induced spinal cord inflammation by promoting A1 polarization of astrocytes via upregulating the C/EBP-β/TGF-β 1 signal pathway, thus leading to neuropathic pain. It was different from the traditional signal pathway, this study shown a new signal pathway for astrocyte A1 polarization, which may provide a possibility for clinical treatment of neuropathic pain.Keywords: neuropathic pain, astrocytes, C/EBP-β, TGF-β 1, neuroinflammation